11. Wykonaj mnożenie i przeprowadź reedukację wyrazów podobnych.
4x - (x + 1)(x - 1) =
(2x - 1)(-3x + 2) - (6x + 3)(-x - 2) =
x[(x + 2)(x - 1)-(x^2– 2)] =​


Odpowiedź :

Odpowiedź:

[tex]4x-(x+1)(x-1)=4x-(x^2-1)=4x-x^2+1=-x^2+4x+1\\\\\\(2x-1)(-3x+2)-(6x+3)(-x-2)=-6x^2+4x+3x-2-(-6x^2-12x-3x-6)=\\\\=-6x^2+7x-2+6x^2+12x+3x+6=22x+4\\\\\\x[(x+2)(x-1)-(x^2-2)]=x(x^2-x+2x-2-x^2+2)=x*x=x^2[/tex]

[tex]1)\\\\4x - (x + 1)(x - 1)=4x - (x^2 -1) =4x - x^2+1=-x^2+4x+1\\\\ 2)\\\\ (2x - 1)(-3x + 2) - (6x + 3)(-x - 2)= \\\\=-6x^2+4x+3x-2 - (-6x^2-12x-3x-6) =\\\\=-6x^2+4x+3x-2 +6x^2+12x+3x+6=22x+4\\\\3)\\\\x[ (x + 2)(x-1)-(x^2-2)] = x (x^2-x+2x-2- x^2+2) = x *x=x^2[/tex]